2008
DOI: 10.1016/j.sab.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Computerized simulation of solute–particle vaporization in an inductively coupled plasma

Abstract: Recent experiments involving aerosol introduction into the inductively coupled plasma have shown that intact droplets and solute particles cause enormous fluctuations in analyte emission and mass-spectral signals. Here, particle-vaporization kinetics are simulated as a detailed function of the operating conditions, fundamental properties and spatial location in the inductively coupled plasma, and as a function of several of the properties of the particles themselves: diameter, chemical composition and size dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…[50][51][52] The ICP conditions for simulation in Fig. The calculation of the rate constants of particle vaporization is based on the combination of heat-transfer and mass-transferlimited vaporization rate models.…”
Section: Nonlinear Calibration Curve Due To Incomplete Vaporizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52] The ICP conditions for simulation in Fig. The calculation of the rate constants of particle vaporization is based on the combination of heat-transfer and mass-transferlimited vaporization rate models.…”
Section: Nonlinear Calibration Curve Due To Incomplete Vaporizationmentioning
confidence: 99%
“…[50][51][52] The boiling point determines the starting position of particle vaporization in the ICP. In the heat-transfer and mass-transfer-limited vaporization mechanisms, the vaporization rate depends on the molecular weight of the analyte and the density of the particle.…”
Section: Simulated Calibration Curvesmentioning
confidence: 99%
“…The temperature of the particles during the melting process is constant at the melting point. The time required for this process is calculated using [27].…”
Section: Particle Meltingmentioning
confidence: 99%
“…It was suggested that it could be attributed to an incomplete vaporization of nanoparticles in the argon plasma or to detection difficulties 26 . Nanoparticle vaporization in the argon plasma can be viewed as a two-stage process: the heat transfer from plasma to particle and the mass transfer from the particle to the plasma 28,29 . In mass transfer limited vaporization, vaporization is controlled by material removal rate from the nanoparticle surface.…”
Section: Calibrationmentioning
confidence: 99%